Genetic diversity of vaginal lactobacilli from women in different countries based on 16S rRNA gene sequences - Pavlova, SI; Kilic, AO; Kilic, SS; So, JS; Nader-Macias, ME; Simoes, JA; Tao, L (Oxford Univ Press, 2002)
Aims: Lactobacilli are widely distributed in food and the environment, and some colonize the human body as commensal bacteria. The aim of this study was to determine the species of lactobacilli that colonize the vagina and compare them with those found in food and the environment. Methods and Results: Thirty-five Lactobacillus strains from women from seven countries were isolated, and sequences from 16S rRNA genes were determined and compared with existing data in GenBank. A phylogenetic tree was achieved using the Neighbour-joining method based on the analysis of 1465 nucleotides. The results showed that most vaginal isolates were L. crispatus, L. jensenii and L. gasseri. Some were L. vaginalis, L. fermentum, L. mucosae, L. paracasei and L. rhamnosus. Two isolates from a native American woman displayed distinct branches, indicating novel phylotypes. Few vaginal isolates matched food or environmental Lactobacillus species. Conclusions: Most women worldwide were colonized by three common Lactobacillus species: L. crispatus, L. jensenii and L. gasseri. Significance and Impact of Study: Knowledge of vaginal Lactobacillus species richness and distribution in women worldwide may lead to the design of better probiotic products as bacterial replacement therapy.
Keywords: Polymorphic Dna (Rapd)-Pcr; Identification; Acidophilus; Plantarum; Nov.